A tool for determining sheltering efficiency of mechanically ventilated buildings against outdoor hazardous agents. (September 2016) - Kulmala, Ilpo; Salmela, Hannu; Kalliohaka, Tapio; Zwęgliński, Tomasz; Smolarkiewicz, Marcin; Taipale, Aimo; Kataja, Jari
Abstract: Sudden large scale outdoor releases of toxic materials may require protective actions in the affected areas, and one option is to shelter indoors. Mechanically ventilated buildings provide protection against outdoor hazardous particulate materials with varying efficiency depending mainly on the properties of the HVAC system of the building, air leakage, and the nature of the outdoor release. A tool for modelling the indoor concentrations due to outdoor contaminants has been developed and presented. The tool solves numerically the simplified mass balance equation describing the size-resolved behaviour of airborne particles and uses as input experimentally obtained data on particle concentrations outdoors, in the supply air, and indoors. By eliminating the effect of indoor sources the size-resolved indoor/outdoor (I/O) ratio for fine particles can be determined accurately, thus giving detailed information on the buildings protective capability and thereby quantitative knowledge to support emergency managers decision making. Highlights: Validated model for size-resolved indoor particle concentration calculation. Method for accurate determination of buildings sheltering efficiency against outdoor pollutants. Advanced wireless indoor air quality measurement system.